Multi-response optimization in precision cutting of wood plastic composites by single-mode fiber laser - Domadi, Mohd Khairul; Ismail, Mohd Idris Shah; Mohd Pisal, Mohd Hanif; Mohamed Yusoff, Mohd Zuhri (Penerbit UTM Press, 2022)
Environmental and sustainability concerns have driven scientists and engineers to prefer bio-composite materials over synthetic fibers. Wood plastic composites (WPCs) are biobased plastic compounds that have gained much attention in diverse engineering applications as eco-friendly and biodegradable solutions that can support global sustainability objectives. However, the complex structures and properties of these composites make them challenging to cut. This study aims to optimize the multiple-response parameters of laser cutting on WPCs containing 30% wood fiber filled with recycled high-density polyethylene (rHDPE) by single-mode fiber laser. A digital microscope measured the kerf width (KW) and heat-affected zone (HAZ). The material removal rate (MRR) was calculated based on the kerf width, material thickness, and cutting speed. In order to identify the optimal combination of cutting parameters for peak power, pulse width, and cutting speed, grey relational analysis (GRA) was utilized. The results of the GRA analysis confirmed that the best performance characteristics for fiber laser cutting of 1 mm thickness of WPC were achieved at a lower peak power of 80 W, a shorter pulse width of 20 µs, and a slower cutting speed of 2 mm/s. The response table indicates that all cutting parameters significantly affect the cutting process, with the cutting speed being the most crucial parameter, followed by peak power and pulse width. This research revealed that multi-response optimization of pulsed fiber laser cutting can result in higher WPC cut quality and improved productivity.